Almost periodic solutions for Abel equations - Zeng Weiyao; Shi Jinlin; Lin Zhensheng; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
Using the Liapunov function method, the existence of almost periodic solutions of a scalar differential equation is discussed The results for the scalar differential equation are then applied to prove the existence and stability of almost periodic solutions of Abel differential equations We obtain several interesting results which improve the results due to Chongyou [1] and Dongpin [2].